Complexometric-Spectrophotometric Determination of Cisapride and Tiapride in Their Formulations - A. Alarfaj, Nawal; A. Mostafa, Azza; A. Alghamdi, Zinah (Asian Journal of Chemistry, 2012)
Simple and sensitive visible spectrophotometric methods were developed for the quantitative determination of cisapride and tiapride in their pharmaceutical formulations. The methods are based on the formation of ion association complexes with acidic dyes, which are extractable into chloroform. Cisapride was determined by its reaction with bromocresol green or bromophenol blue at pH 2.5 to yield yellow coloured complexes, peaking at 414 nm and 412 nm with bromocresol green and bromophenol blue respectively. Tiapride was determined by its reaction with tropaeolin OO(TOO) at pH 5 to yield a yellowish ion-pair complex measured at 412 nm. Good linearities were achieved in the range of 5-22.5 μg/mL cisapride with both bromocresol green and bromophenol blue and 4-20 μg/mL tiapride with mean recoveries of 100.0 ± 0.28, 100.4 ± 0.94 and 99.9 ± 0.72 %, respectively. The proposed methods were successfully applied to analyze both drugs in their tablets.